Deteksi Tingkat Gangguan Kecemasan Menggunakan Metode Random Forest - Fadhilah, Ghefira Zahra Nur; Saputra, Rizal Adi; Wibowo, Asa Hari (Jurnal Teknik, 2024)
Abstract Anxiety is something that must exist in life, so everyone must have it. In everyday life, having anxiety is normal, but excessive anxiety can lead to self-stabilization disorders so that it is classified as an anxiety disorder. With reference to these conditions, this research was conducted with the aim of identifying the early stages of anxiety disorders using the Data Mining process and the Random Forest algorithm. This research applies the Knowledge Discovery in Database (KDD) method for data processing and uses the GAD-7 questionnaire in data collection with a total of 670 records. This study also applied 10-fold cross validation for model evaluation with specificity, sensitivity, and accuracy parameters. The final results of the study show that the prediction of anxiety levels with the Random Forest algorithm has an accuracy rate of 89.55%. Of the total respondents, 12.99% were categorized as normal or not experiencing anxiety disorders, 28.06% experienced mild anxiety disorders, 32.84% experienced moderate anxiety, and 26.12% experienced severe anxiety.Abstrak Kecemasan adalah suatu hal yang pasti ada dalam kehidupan, sehingga semua orang pasti memilikinya. Dalam kehidupan sehari-hari memiliki kecemasan adalah hal yang normal, tetapi kecemasan yang berlebihan dapat mengakibatkan gangguan kestabilan diri sehingga diklasifikasikan sebagai gangguan kecemasan. Dengan merujuk dari kondisi tersebut, penelitian ini dilakukan dengan tujuan mengidentifikasi tahap awal gangguan kecemasan dengan menggunakan proses Data Mining dan algoritma Random Forest. Penelitian ini menerapkan metode Knowledge Discovery in Database (KDD) untuk pemrosesan data dan menggunakan kuesioner GAD-7 dalam pengumpulan data dengan banyak responden 670 record. Penelitian ini juga menerapkan 10-fold cross validation untuk evaluasi model dengan paramater spesifisitas, sensitivitas, dan akurasi. Hasil akhir dari penelitian ini menunjukkan bahwa hasil prediksi tingkat kecemasan dengan algoritma Random Forest memiliki tingkat akurasi 89,55%. Dari total responden, 12,99% dikategorikan normal atau tidak mengalami gangguan kecemasan, 28,06% mengalami gangguan kecemasan ringan, 32,84% mengalami kecemasan sedang, dan 26,12% mengalami kecemasan berat.